Colliding Identities During COVID-19: Identifying and Addressing the Challenges of Being an Academic Mother During a Global Pandemic - Harrop, Gill (Frontiers in Education, 2021)
Academic workloads require a careful balance of teaching, research, supervision, and administrative responsibilities. Being an academic parent adds an additional level of responsibility to this, which has traditionally been successfully managed with organisation, careful planning and support. For many academic parents the Covid-19 pandemic disrupted this carefully curated balance, forcing them to work from home while also dealing with the loss of childcare and the requirement to provide homeschooling. The pre-existing gender disparity in childcare and housework was exacerbated by lockdown, with a disproportionate impact on academic mothers who were often forced to take on additional childcare and housework responsibilities, alongside remote schooling. The gender disparity further affected job stability, with women losing a greater number of paid working hours during the pandemic and having greater employment instability. This article reflects upon the impact of gender disparity in academic parents during the Covid-19 pandemic, and considers potential barriers to productivity and progression, including the role of interruptions, delivering sensitive materials in a workspace shared with children and technological challenges.